النظام الإنتخابي الجزائري ودوره في تعزيز الديمقراطية المحلية - الوافي, سامي (Revue jurisprudence, 2018)
تعد الإنتخابات الحرة والنزيهة أحد ركائز الديمقراطية ومقياسا لها، بل الوسيلة المثلى والمشروعة لإسناد السلطة، ف الإنتخابات تمثل فاعلا محوريا في ترسيخ الديمقراطية وتمكين المواطنين من ممارسة حقوقه م السياسية والمدنية من خلالها . و على المستوى المحلي ف إن الإنتخاب ات ت عد همزة وصل تربط الديمقراطية باللامركزية الإدارية، فضلا عن كونه ا ركن في النظرية اللامركزية الإدارية لأنه ا شرط أساسي لتحقيق إ ستقلال المجالس المحلية، وأساس بناء الديمقراطية المحلية ووسيلة لتجسيد إشراك الشعب في السلطة وإشراكه في صنع القرار السياسي . ولقيام أي نظام ديمقراطي حقيقي يتطلب أن تعمل الدولة على كفالة الحقوق السياسية وحمايتها بنصوص دستورية وقانونية بالقدر الذي يشجع مواطنيها على المشاركة في الإنتخابات وذلك بترجيح القانون على أي إعتبار في كل الظروف لضمان قاعدة حرية إختيار الشعب لممثليه . ويسعي المشرع الجزائري من خلال مراجعة التشريعات الإنتخابية وتعديلها نحو تجسيد نظام إنتخابي شفاف يكرس الديمقراطية سيما على المستوى المحلي، فإلى أي مدى تمكنت التشريعات الإنتخابية في الجزائر من تجسيد منظومة إنتخابية توطد دعائم الديمقراطية المحلية ؟ الكلمات المفتاحية : الديمقراطية، النظام الإنتخابي، اللامركزية . Summary   The free and fair elections are one of the pillars of democracy and a measure of it, but the best and legitimate means of attributing power, elections are a pivotal actor in the consolidation of democracy and the empowerment of citizens to exercise their political and civil rights. At the local level, elections are a link between democracy and administrative decentralization, as well as being a cornerstone of administrative decentralization because it is a prerequisite for achieving the independence of local councils, the basis for building local democracy and a means of embodying the people's involvement in power and involving it in Political decision-making . For a truly democratic system, a State must ensure that political rights are safeguarded and protected by constitutional and legal provisions to the extent that it encourages its citizens to participate in elections by weighting the law to any consideration in all circumstances to ensure the rule of free choice of the people of the Representative Why. The Algerian legislator seeks to revise the electoral legislation and amend it towards the embodiment of a transparent electoral system that enshrines democracy, particularly at the level local, to what extent has electoral legislation in Algeria been able to embody an electoral system that consolidates the foundations of local democracy? Keywords: democracy, the electoral system and decentralization